Sustainably-utilized composite material for food packaging and preparation process thereof

By coating the PET substrate with a high oxygen moisture barrier coating and a high-strength film material solution, the problems of non-renewable and insufficient gas moisture barrier properties of traditional food packaging materials are solved, and a food packaging composite with sustainable utilization and high barrier properties is achieved. Material.

CN119331291AActive Publication Date: 2025-01-21GUANGDONG LABORATORY OF CHEMISTRY & FINE CHEMICAL IND JIEYANG CENTER JIEYANG +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411458081.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Traditional food packaging materials such as PET materials have problems such as non-renewable, difficult to degrade, high energy consumption and insufficient gas moisture barrier performance, which limits their application scope.

Method used

Develop a sustainable composite material for food packaging. By preparing a high oxygen moisture barrier coating and a high-strength film solution, and coating them on a PET substrate, a composite material with excellent mechanical properties and high barrier properties is formed. .

Benefits of technology

It enables composite materials to maintain excellent mechanical properties during recycling, avoids frequent recycling, saves energy, and greatly improves the oxygen and moisture barrier capabilities to meet the needs of most food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331291A_ABST
    Figure CN119331291A_ABST
Patent Text Reader

Abstract

The invention relates to the field of packaging materials, in particular to a sustainable composite material for food packaging and a preparation process thereof. Comprising the following steps: preparing an oxygen and moisture high-barrier coating; preparing a high-strength membrane material solution; and carrying out surface treatment on the PET base material and coating a film layer. Through the synergistic effect of the rice bran wax and cinnamyl aldehyde, the hydrophilicity of polyvinyl alcohol is inhibited, a compact membrane structure is formed, the mechanical strength and the barrier property to moisture and oxygen of a membrane layer are enhanced, cinnamyl alcohol can provide good oxidation resistance and antibacterial property for the membrane layer, ZnO can be embedded into a coating structure to fill micropores and defects, and the barrier property to water and oxygen is improved. In conclusion, the barrier ability of the sustainable composite material for food packaging to oxygen and moisture is greatly improved, and the composite material has good antibacterial and antioxidant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of packaging materials, and in particular to a sustainable composite material for food packaging and a preparation process thereof. Background Art

[0002] As people's environmental awareness increases, the food packaging industry has an increasing demand for sustainable packaging materials. Traditional food packaging materials, especially plastic materials, although they have good air tightness and moisture resistance, are often difficult to reuse and easy to pollute the environment. In recent years, how to develop sustainable packaging materials while ensuring food safety has become the focus of academia and industry.

[0003] Polyethylene terephthalate (PET) is a widely used food packaging material with high transparency and good gas barrier properties. However, since the main raw material of PET material comes from petroleum, it is a non-renewable resource and difficult to degrade in the natural environment, resulting in high energy consumption during the recycling process, which easily causes material waste and produces harmful chemicals, increasing the burden on the environment. At the same time, in some high-demand packaging applications, the barrier properties of PET material to gas and moisture still do not meet the requirements, limiting the application scope of polyethylene terephthalate. Summary of the invention

[0004] In order to solve the above-mentioned technical defects, the present invention has developed a sustainable composite material for food packaging and a preparation process thereof. The prepared sustainable composite material for food packaging has good antibacterial properties and can maintain excellent mechanical properties during recycling, so that it can be continuously utilized, avoiding the need for frequent recycling, saving energy, and having high barrier properties to gas and moisture, meeting the needs of most food packaging.

[0005] A process for preparing a composite material for food packaging that can be sustainably utilized comprises the following steps:

[0006] S1: Preparation of high oxygen and moisture barrier coatings

[0007] The rice bran wax is melted and filtered, and then coated on the surface of the carrier, and then cooled to obtain a rice bran wax film, 3-aminopropyl triethoxysilane is mixed with anhydrous ethanol, and then an acid reagent is added, and stirred to obtain an APTES solution, and the rice bran wax film is immersed in the APTES solution, stirred and then allowed to stand, and then filtered to obtain a solid, and the solid is washed and dried to obtain a modified rice bran wax, and the modified rice bran wax and cinnamaldehyde are added to deionized water, and the temperature is increased and stirred in a water bath to obtain a premixed liquid, polyvinyl alcohol is dissolved in hot deionized water to obtain a polyvinyl alcohol solution I, and nano ZnO is ultrasonically dispersed in deionized water to obtain a ZnO dispersion, and then the polyvinyl alcohol solution I and the ZnO dispersion are uniformly mixed to obtain a suspension, the suspension and the premixed liquid are uniformly mixed and stirred, and the pH is adjusted and then heated in a water bath, and then ultrasonically treated to obtain a high oxygen and moisture barrier coating;

[0008] S2: Preparation of high-strength membrane solution

[0009] The silk is placed in a Na2CO3 aqueous solution for heating treatment, washed and dried to obtain degummed silk, the degummed silk is added to a dissolving solution, heated and stirred until completely dissolved to obtain a silk fibroin mixed solution, the silk fibroin mixed solution is dialyzed with deionized water to obtain a silk fibroin aqueous solution, polyvinyl alcohol is dissolved in deionized water to obtain a polyvinyl alcohol solution II, corn starch nanocrystals are ultrasonically dispersed in deionized water to obtain a corn starch nanocrystal dispersion, the silk fibroin aqueous solution and the polyvinyl alcohol solution II are uniformly mixed, fumaric acid is added and stirred, and then glycerol and the corn starch nanocrystal dispersion are added for high-speed shearing, and a high-strength membrane material solution is obtained after standing.

[0010] S3: Surface treatment and film coating of PET substrate

[0011] The PET substrate is cleaned and subjected to graded corona treatment to obtain a surface-treated PET substrate. A high-strength film material solution is evenly coated on the surface of the surface-treated PET substrate using a coating rod. After drying, a film-coated PET substrate is obtained. A coating rod is then used to evenly coat the oxygen and moisture high barrier coating on the surface of the film-coated PET substrate. Drying is continued to obtain a sustainable composite material for food packaging.

[0012] Furthermore, step S1 of preparing the oxygen and moisture high barrier coating comprises the following steps:

[0013] S1.1: Heat the rice bran wax until it is completely melted, filter to remove impurities, and then evenly coat the wax on the surface of the carrier by roller coating, controlling the coating thickness to be 1-2 mm, and obtain a rice bran wax film after cooling to room temperature, and place 3-aminopropyltriethoxysilane and anhydrous ethanol in a volume ratio of 1: (20-30) in a container, then add 1-2 wt % of an acid reagent, and stir evenly to obtain an APTES solution;

[0014] S1.2: Immerse the rice bran wax film in the APTES solution, stir for 20-30 minutes, let stand for 1-1.5 hours, and then filter to obtain a solid, rinse the solid with anhydrous ethanol for 1-2 minutes, rinse it in deionized water for 2-3 times, and then dry it in a drying oven at a temperature of 40-45° C. for 2-3 hours to obtain modified rice bran wax, add 1-2 parts by weight of modified rice bran wax and 0.4-0.5 parts by weight of cinnamaldehyde to 30-40 parts by weight of deionized water, and stir it in a water bath at 50-55° C. for 50-60 minutes to obtain a premix;

[0015] S1.3: Dissolve 12-15 parts by weight of polyvinyl alcohol in deionized water at 95-98°C to prepare a polyvinyl alcohol solution I with a mass fraction of 20-25%, mix 1-1.5 parts by weight of nano ZnO and 50-60 parts by weight of deionized water and place them in an ultrasonic cleaning machine, ultrasonicate at an ultrasonic frequency of 25-30kHz for 10-12 minutes to obtain a ZnO dispersion, then mix the polyvinyl alcohol solution I and the ZnO dispersion in a mass ratio of 1:(0.8-1) in a container, stir for 25-30 minutes to obtain a suspension, stir the premixed solution and the suspension obtained in step S1.2 at high speed to uniformly mix, adjust the pH to 2-3, place in a water bath, heat at a water bath temperature of 60-65°C for 1-2 hours, and then ultrasonicate at an ultrasonic frequency of 25-30kHz for 20-30 minutes to obtain a high oxygen and moisture barrier coating.

[0016] Furthermore, step S2 prepares a high-strength membrane material solution, comprising the following steps:

[0017] S2.1: placing silk in a 0.05-0.06% Na2CO3 aqueous solution, heating at 98-100°C for 30-35 minutes, repeating 2-3 times, washing with deionized water and drying to obtain degummed silk, adding the degummed silk to the dissolving solution, stirring at 70-75°C until the degummed silk is completely dissolved, obtaining a fibroin mixed solution, placing the fibroin mixed solution into a dialysis bag, dialyzing with deionized water for 4-5 days, obtaining a fibroin aqueous solution;

[0018] S2.2: dissolving polyvinyl alcohol in deionized water at 95-98° C. to prepare a 5-6 wt % polyvinyl alcohol solution II, and then placing corn starch nanocrystals and deionized water in an ultrasonic disperser, and ultrasonically dispersing them at an ultrasonic frequency of 25-30 kHz for 10-15 minutes to prepare a 0.6-0.8 wt % corn starch nanocrystal dispersion;

[0019] S2.3: Mix the silk fibroin aqueous solution and polyvinyl alcohol solution II in a volume ratio of 1:(0.8-1) in a container, stir evenly and add fumaric acid. After stirring for 1-2 hours, add glycerol and corn starch nanocrystal dispersion, shear at a speed of 2000-3000 rpm for 40-45 minutes, and then let it stand for 2-3 hours to obtain a high-strength membrane solution.

[0020] Furthermore, step S3 of surface treatment of the PET substrate and film coating comprises the following steps:

[0021] S3.1: Clean the surface of the PET substrate, then place it in a corona machine, set the distance between the electric blade and the PET substrate to 4-5mm, the voltage to 6-8kV, the pulse frequency to 32-35kHz, start the corona machine for 10-15 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 6-8mm, the voltage to 8.5-9kV, the pulse frequency to 20-25kHz, start the corona machine for 10-12 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 10-12mm, the voltage to 9.5-11kV, the pulse frequency to 18-20kHz, start the corona machine for 15-20 minutes of corona treatment, and obtain a surface-treated PET substrate;

[0022] S3.2: Use a coating rod with a wet film thickness of 8-10μm to evenly coat the high-strength film material solution on the surface of the surface-treated PET substrate, and then place it in a blower dryer for drying for 12-15 hours to obtain a coated PET substrate. Then use a 6-8μm coating rod to evenly coat the oxygen and moisture high barrier coating on the surface of the coated PET substrate, and continue to place it in a blower dryer for drying for 10-12 hours to obtain a sustainable composite material for food packaging.

[0023] Furthermore, the acid reagent in step S1.1 is acetic acid.

[0024] Furthermore, the stirring speed of the high-speed stirring in step S1.3 is 1200-1500 rpm.

[0025] Furthermore, in step S1.3, the pH is adjusted by adding a hydrochloric acid solution with a concentration of 20-25%.

[0026] Furthermore, the dissolving solution in step S2.1 is prepared from CaCl2, ethanol and water in a molar ratio of 1:(2-3):(8-10).

[0027] Furthermore, in step S2.3, the fumaric acid accounts for 0.5-1% of the total mass of the silk fibroin aqueous solution and the polyvinyl alcohol solution, the glycerol accounts for 25-30% of the total volume of the silk fibroin aqueous solution and the polyvinyl alcohol solution, and the corn starch nanocrystal dispersion accounts for 40-50% of the total volume of the silk fibroin aqueous solution and the polyvinyl alcohol solution.

[0028] A composite material for food packaging that can be sustainably utilized is prepared by the above-mentioned preparation process of the composite material for food packaging that can be sustainably utilized.

[0029] The beneficial effects are as follows: 1. The rice bran wax is immersed in an APTES solution and amino groups are introduced onto the surface to obtain the modified rice bran wax, which is then stirred in a heated water bath with cinnamaldehyde. During this process, the aldehyde group and the amino group undergo a Schiff base reaction to obtain a premixed liquid, thereby improving the binding ability of the rice bran wax with subsequent polyvinyl alcohol. The premixed liquid is then mixed with polyvinyl alcohol solution I and a ZnO dispersion liquid, and subjected to a heated water bath and ultrasonic treatment to obtain a high oxygen and moisture barrier coating, wherein the imine produced by the Schiff base reaction of the rice bran wax and cinnamaldehyde can undergo a cross-linking reaction with the polyvinyl alcohol, and the two can synergistically inhibit the hydrophilicity of the polyvinyl alcohol and form a dense film structure, thereby enhancing the mechanical strength of the film layer and the barrier performance to water and oxygen, and cinnamyl alcohol can also provide the film layer with good antioxidant and antibacterial properties, and ZnO can be embedded in the coating structure to fill micropores and defects, thereby improving the density and mechanical strength of the film layer. In summary, the coating on the PET substrate greatly improves the barrier capacity of the sustainable food packaging composite material to oxygen and moisture, and enables it to have good antibacterial and antioxidant properties.

[0030] 2. The present invention uses silk fibroin as the main raw material and fumaric acid as a cross-linking agent, which first undergoes a pre-cross-linking reaction with polyvinyl alcohol, and then adds glycerol and corn starch nanocrystals to introduce into the crystallization domain. The fumaric acid reacts with a large number of hydroxyl groups and amino groups in each component to form a large number of hydrogen bonds. The crystallization domains and hydrogen bonds can act as sacrificial bonds to dissipate energy in the high-strength film material, thereby giving the high-strength film material excellent mechanical properties. In addition, since the crystallization domains and hydrogen bonds have dynamic recoverability, the high-strength film material is coated on a PET substrate, so that the prepared composite material for food packaging can still maintain excellent mechanical properties after recycling, so that it can be continuously utilized and avoids frequent recycling of PET materials.

[0031] 3. The present invention significantly improves the surface tension of the PET substrate by performing graded corona treatment on the PET substrate, and can evenly distribute the surface tension of the PET substrate, thereby reducing the decrease in mechanical strength of the PET substrate after corona treatment, significantly improving the adhesion between the high-strength film material solution and the PET substrate, and improving the overall strength and stability of the composite material for sustainable food packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a process flow chart of preparing a sustainable composite material for food packaging used in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1: A sustainable composite material for food packaging and its preparation process, such as Figure 1 As shown, the following steps are included:

[0035] S1: Preparation of high oxygen and moisture barrier coatings

[0036] S1.1: Heat the rice bran wax until it is completely melted, filter to remove impurities, and then evenly coat it on the surface of the carrier by roller coating, controlling the coating thickness to be 1 mm, and obtain a rice bran wax film after cooling to room temperature, and mix 3-aminopropyltriethoxysilane and anhydrous ethanol in a volume ratio of 1:20 in a container, then add 1wt% acetic acid, and stir evenly to obtain an APTES solution;

[0037] S1.2: Immerse the rice bran wax film in the APTES solution, stir for 20 minutes, let stand for 1 hour, and then filter to obtain a solid, rinse the solid with anhydrous ethanol for 1 minute, rinse it in deionized water twice, and then dry it in a drying oven at 40° C. for 2 hours to obtain modified rice bran wax, add 1 part by weight of modified rice bran wax and 0.4 parts by weight of cinnamaldehyde to 30 parts by weight of deionized water, and stir it in a 50° C. water bath for 50 minutes to obtain a premix;

[0038] S1.3: Dissolve 12 parts by weight of polyvinyl alcohol in deionized water at 95°C to prepare a polyvinyl alcohol solution I with a mass fraction of 20%. Mix 1 part by weight of nano ZnO and 50 parts by weight of deionized water and place them in an ultrasonic cleaning machine. Ultrasonicate at an ultrasonic frequency of 25 kHz for 10 minutes to obtain a ZnO dispersion. Then mix the polyvinyl alcohol solution I and the ZnO dispersion in a mass ratio of 1:0.8 in a container and stir for 25 minutes to obtain a suspension. Stir the premix and suspension obtained in step S1.2 at a stirring speed of 1200 rpm, add a 25% hydrochloric acid solution to adjust the pH to 2, and then place it in a water bath. Heat it at a water bath temperature of 60°C for 1 hour, and then ultrasonicate it at an ultrasonic frequency of 25 kHz for 20 minutes to obtain a high oxygen and moisture barrier coating.

[0039] S2: Preparation of high-strength membrane solution

[0040] S2.1: placing silk in a 0.05% Na2CO3 aqueous solution, heating at 98°C for 30 minutes, repeating twice, washing with deionized water and drying to obtain degummed silk, adding the degummed silk to a dissolving solution prepared by CaCl2, ethanol and water in a molar ratio of 1:2:8, stirring at 70°C until the degummed silk is completely dissolved to obtain a silk fibroin mixed solution, placing the silk fibroin mixed solution into a dialysis bag, dialyzing with deionized water for 4 days to obtain a silk fibroin aqueous solution;

[0041] S2.2: polyvinyl alcohol was dissolved in deionized water at 95°C to prepare a 5 wt% polyvinyl alcohol solution II, and then corn starch nanocrystals and deionized water were placed in an ultrasonic disperser and ultrasonically dispersed at an ultrasonic frequency of 25 kHz for 10 minutes to prepare a 0.6 wt% corn starch nanocrystal dispersion;

[0042] S2.3: Mix the silk fibroin aqueous solution and polyvinyl alcohol solution II in a volume ratio of 1:0.8 and place them in a container. After stirring evenly, add 0.5% fumaric acid based on the total mass of the silk fibroin aqueous solution and polyvinyl alcohol solution. After stirring for 1 hour, add glycerol accounting for 25% of the total volume of the silk fibroin aqueous solution and polyvinyl alcohol solution and 40% corn starch nanocrystal dispersion. After high-speed shearing at a speed of 2000 rpm for 40 minutes, let it stand for 2 hours to obtain a high-strength membrane solution.

[0043] S3: Surface treatment and film coating of PET substrate

[0044] S3.1: Clean the surface of the PET substrate, and then place it in a corona machine, set the distance between the electric blade and the PET substrate to 4 mm, the voltage to 6 kV, the pulse frequency to 32 kHz, start the corona machine for 15 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 6 mm, the voltage to 8.5 kV, the pulse frequency to 20 kHz, start the corona machine for 12 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 10 mm, the voltage to 9.5 kV, the pulse frequency to 18 kHz, start the corona machine for 20 minutes of corona treatment, and obtain a surface-treated PET substrate;

[0045] S3.2: Use a coating rod with a wet film thickness of 8μm to evenly coat the high-strength film material solution on the surface of the surface-treated PET substrate, and then place it in a blower dryer for 12 hours to obtain a coated PET substrate. Then use a 6μm coating rod to evenly coat the oxygen and moisture high barrier coating on the surface of the coated PET substrate, and continue to place it in a blower dryer for 10 hours to obtain a sustainable composite material for food packaging.

[0046] Example 2: A sustainable composite material for food packaging and its preparation process, such as Figure 1 As shown, the following steps are included:

[0047] S1: Preparation of high oxygen and moisture barrier coatings

[0048] S1.1: Heat the rice bran wax until it is completely melted, filter to remove impurities, and then evenly coat it on the surface of the carrier by roller coating, controlling the coating thickness to be 1 mm, and obtain a rice bran wax film after cooling to room temperature, and mix 3-aminopropyltriethoxysilane and anhydrous ethanol in a volume ratio of 1:20 in a container, then add 1wt% acetic acid, and stir evenly to obtain an APTES solution;

[0049] S1.2: Immerse the rice bran wax film in the APTES solution, stir for 20 minutes, let stand for 1 hour, and then filter to obtain a solid, rinse the solid with anhydrous ethanol for 1 minute, rinse it in deionized water twice, and then dry it in a drying oven at 40° C. for 2 hours to obtain modified rice bran wax, add 2 parts by weight of modified rice bran wax and 0.5 parts by weight of cinnamaldehyde to 40 parts by weight of deionized water, and stir it in a 50° C. water bath for 50 minutes to obtain a premix;

[0050] S1.3: Dissolve 15 parts by weight of polyvinyl alcohol in deionized water at 95°C to prepare a polyvinyl alcohol solution I with a mass fraction of 25%. Mix 1.5 parts by weight of nano ZnO and 60 parts by weight of deionized water and place them in an ultrasonic cleaner. Ultrasonicate at an ultrasonic frequency of 25 kHz for 10 minutes to obtain a ZnO dispersion. Then mix the polyvinyl alcohol solution I and the ZnO dispersion in a mass ratio of 1:1 in a container and stir for 25 minutes to obtain a suspension. Stir the premix and the suspension obtained in step S1.2 at a stirring speed of 1200 rpm, add a 25% hydrochloric acid solution to adjust the pH to 2, and then place it in a water bath. Heat it at a water bath temperature of 60°C for 1 hour, and then ultrasonicate it at an ultrasonic frequency of 25 kHz for 20 minutes to obtain a high oxygen and moisture barrier coating.

[0051] S2: Preparation of high-strength membrane solution

[0052] S2.1: placing silk in a 0.05% Na2CO3 aqueous solution, heating at 98°C for 30 minutes, repeating twice, washing with deionized water and drying to obtain degummed silk, adding the degummed silk to a dissolving solution prepared by CaCl2, ethanol and water in a molar ratio of 1:2:8, stirring at 70°C until the degummed silk is completely dissolved to obtain a silk fibroin mixed solution, placing the silk fibroin mixed solution into a dialysis bag, dialyzing with deionized water for 4 days to obtain a silk fibroin aqueous solution;

[0053] S2.2: polyvinyl alcohol was dissolved in deionized water at 95°C to prepare a 6 wt% polyvinyl alcohol solution II, and then corn starch nanocrystals and deionized water were placed in an ultrasonic disperser and ultrasonically dispersed at an ultrasonic frequency of 25 kHz for 10 minutes to prepare a 0.8 wt% corn starch nanocrystal dispersion;

[0054] S2.3: Mix the silk fibroin aqueous solution and polyvinyl alcohol solution II in a volume ratio of 1:1 in a container, stir evenly, add 1% fumaric acid based on the total mass of the silk fibroin aqueous solution and polyvinyl alcohol solution, stir for 1 hour, add 30% glycerol based on the total volume of the silk fibroin aqueous solution and polyvinyl alcohol solution and 50% corn starch nanocrystal dispersion, shear at a high speed of 2000 rpm for 40 minutes, then let stand for 2 hours to obtain a high-strength membrane solution.

[0055] S3: Surface treatment and film coating of PET substrate

[0056] S3.1: Clean the surface of the PET substrate, and then place it in a corona machine, set the distance between the electric blade and the PET substrate to 4 mm, the voltage to 6 kV, the pulse frequency to 32 kHz, start the corona machine for 15 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 6 mm, the voltage to 8.5 kV, the pulse frequency to 20 kHz, start the corona machine for 12 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 10 mm, the voltage to 9.5 kV, the pulse frequency to 18 kHz, start the corona machine for 20 minutes of corona treatment, and obtain a surface-treated PET substrate;

[0057] S3.2: Use a coating rod with a wet film thickness of 8μm to evenly coat the high-strength film material solution on the surface of the surface-treated PET substrate, and then place it in a blower dryer for 12 hours to obtain a coated PET substrate. Then use a 6μm coating rod to evenly coat the oxygen and moisture high barrier coating on the surface of the coated PET substrate, and continue to place it in a blower dryer for 10 hours to obtain a sustainable composite material for food packaging.

[0058] Example 3: A sustainable composite material for food packaging and its preparation process, such as Figure 1 As shown, the following steps are included:

[0059] S1: Preparation of high oxygen and moisture barrier coatings

[0060] S1.1: Heat the rice bran wax until it is completely melted, filter to remove impurities, and then evenly coat it on the surface of the carrier by roller coating, controlling the coating thickness to be 2 mm, and obtain a rice bran wax film after cooling to room temperature, and mix 3-aminopropyltriethoxysilane and anhydrous ethanol in a volume ratio of 1:30 in a container, and then add 2wt% of acetic acid, and stir evenly to obtain an APTES solution;

[0061] S1.2: Immerse the rice bran wax film in the APTES solution, stir for 30 minutes, let stand for 1.5 hours, and then filter to obtain a solid. Rinse the solid with anhydrous ethanol for 2 minutes, rinse it in deionized water for 3 times, and then dry it in a drying oven at 45° C. for 3 hours to obtain a modified rice bran wax. Add 1 part by weight of the modified rice bran wax and 0.4 parts by weight of cinnamaldehyde to 30 parts by weight of deionized water, and stir it in a 55° C. water bath for 60 minutes to obtain a premixed solution.

[0062] S1.3: Dissolve 12 parts by weight of polyvinyl alcohol in deionized water at 98°C to prepare a polyvinyl alcohol solution I with a mass fraction of 20%. Mix 1 part by weight of nano ZnO and 50 parts by weight of deionized water and place them in an ultrasonic cleaning machine. Ultrasonicate at an ultrasonic frequency of 30 kHz for 12 minutes to obtain a ZnO dispersion. Then mix the polyvinyl alcohol solution I and the ZnO dispersion in a mass ratio of 1:0.8 in a container and stir for 30 minutes to obtain a suspension. Stir the premix and suspension obtained in step S1.2 at a stirring speed of 1500 rpm, add a 20% hydrochloric acid solution to adjust the pH to 3, and then place it in a water bath. Heat it at a water bath temperature of 65°C for 2 hours, and then ultrasonicate it at an ultrasonic frequency of 30 kHz for 30 minutes to obtain a high oxygen and moisture barrier coating.

[0063] S2: Preparation of high-strength membrane solution

[0064] S2.1: placing silk in a 0.06% Na2CO3 aqueous solution, heating at 100°C for 35 minutes, repeating 3 times, washing with deionized water and drying to obtain degummed silk, adding the degummed silk to a dissolving solution prepared by CaCl2, ethanol and water in a molar ratio of 1:3:10, stirring at 75°C until the degummed silk is completely dissolved to obtain a silk fibroin mixed solution, placing the silk fibroin mixed solution into a dialysis bag, dialyzing with deionized water for 5 days to obtain a silk fibroin aqueous solution;

[0065] S2.2: polyvinyl alcohol was dissolved in deionized water at 98°C to prepare a 6 wt% polyvinyl alcohol solution II, and then corn starch nanocrystals and deionized water were placed in an ultrasonic disperser and ultrasonically dispersed at an ultrasonic frequency of 30 kHz for 15 minutes to prepare a 0.6 wt% corn starch nanocrystal dispersion;

[0066] S2.3: Mix the silk fibroin aqueous solution and polyvinyl alcohol solution II in a volume ratio of 1:0.8 and place them in a container. After stirring evenly, add 0.5% fumaric acid based on the total mass of the silk fibroin aqueous solution and the polyvinyl alcohol solution. After stirring for 2 hours, add glycerol accounting for 25% of the total volume of the silk fibroin aqueous solution and the polyvinyl alcohol solution and 40% corn starch nanocrystal dispersion. After high-speed shearing at a rotation speed of 3000 rpm for 45 minutes, let it stand for 3 hours to obtain a high-strength membrane solution.

[0067] S3: Surface treatment and film coating of PET substrate

[0068] S3.1: Clean the surface of the PET substrate, then place it in a corona machine, set the distance between the electric blade and the PET substrate to 5 mm, the voltage to 8 kV, the pulse frequency to 35 kHz, start the corona machine for 10 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 8 mm, the voltage to 9 kV, the pulse frequency to 25 kHz, start the corona machine for 10 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 12 mm, the voltage to 11 kV, the pulse frequency to 20 kHz, start the corona machine for 15 minutes of corona treatment, and obtain a surface-treated PET substrate;

[0069] S3.2: Use a coating rod with a wet film thickness of 10μm to evenly coat the high-strength film material solution on the surface of the surface-treated PET substrate, and then place it in a blower dryer for 15 hours to obtain a coated PET substrate. Then use an 8μm coating rod to evenly coat the oxygen and moisture high barrier coating on the surface of the coated PET substrate, and continue to place it in a blower dryer for 12 hours to obtain a sustainable composite material for food packaging.

[0070] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 removes step S1.1 and step S1.2, and no premix is ​​added in step S1.3. The remaining steps are the same as those in Example 1, and a sustainable composite material for food packaging is prepared, which is recorded as Comparative Example 1.

[0071] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 removes step S1.1 and does not add modified rice bran wax in step S1.2. The remaining steps are the same as Example 1 to prepare a sustainable composite material for food packaging, which is recorded as Comparative Example 2.

[0072] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that cinnamaldehyde is not added in step S1.2 of Comparative Example 3, and the remaining steps are the same as those of Example 1 to prepare a sustainable composite material for food packaging, which is recorded as Comparative Example 3.

[0073] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 removes step S2, and in step S3.2, the surface-treated PET substrate is not coated with a high-strength film material solution. The remaining steps are the same as Example 1, and a sustainable composite material for food packaging is obtained, which is recorded as Comparative Example 4.

[0074] Experiment 1: Take the sustainable composite material for food packaging prepared in Example and Comparative Examples 1-3, refer to "GB / T1034-2008 Test of Water Absorption of Plastics", and perform water absorption treatment on the sustainable composite material for food packaging for 12 hours, and calculate the water absorption rate according to the formula water absorption rate = (m2-m1) / m1×100%, where m2 is the weight after water absorption and m1 is the weight before water absorption. According to the determination of "GB / T26253-2010 Water Vapor Permeability of Plastic Film and Thin Sheet", the water vapor barrier performance is tested, and then according to "GB / T1038-2000 Plastic Film and Thin Sheet Gas Permeability Test Method Pressure Difference Method" the oxygen barrier performance is tested. Each group of experiments is carried out three times, the average value is taken, and the data is recorded and tabulated, as shown in Table 1.

[0075] Table 1: Water absorption, water vapor and oxygen transmission rates of sustainable food packaging composite materials

[0076] Water absorption / % <![CDATA[Water vapor transmission rate g / (m 2 ·day)]]> <![CDATA[Oxygen transmission rate g / (m 2 ·day)]]> Example 1 5.3 2.2 1.2 Example 2 5.1 2.1 1.2 Example 3 4.8 1.8 1 Comparative Example 1 26.3 42.3 81.4 Comparative Example 2 18.6 25.6 47.9 Comparative Example 3 15.3 20.1 44.3

[0077] It can be seen from Table 1 that the water absorption, water vapor permeability and oxygen permeability of the composite material for sustainable food packaging prepared in the embodiment are all lower than those of comparative examples 1-3, which proves that the modified rice bran wax and cinnamaldehyde are combined with polyvinyl alcohol to prepare a high oxygen and moisture barrier coating, which can greatly improve the barrier ability of the composite material for sustainable food packaging to oxygen and moisture. It can be seen that the increased values ​​of the water absorption, water vapor permeability and oxygen permeability of comparative example 1 relative to that of embodiment 1 are lower than the sum of the increased values ​​of the water absorption, water vapor permeability and oxygen permeability of comparative examples 2 and 3, which proves that the modified rice bran wax and cinnamaldehyde synergistically improve the barrier properties of the composite material for sustainable food packaging to moisture and oxygen.

[0078] Experiment 2: The sustainable composite material for food packaging prepared in the embodiment and comparative examples 1-4 of the same shape and size were respectively clamped on an electronic universal testing machine for film materials. The tensile force was 30N, the initial clamp was set to 20mm, the gauge length was set to 10mm, the stretching rate was set to 30mm / min, and the stretching distance at break was tested under room temperature. The longer the stretching distance, the better the tensile strength. Each test was performed three times, and the data were recorded and tabulated, as shown in Table 2.

[0079] Table 2: The tensile distance of sustainable food packaging composite materials under 30N tensile force

[0080] Stretching distance / mm first Second time The third time Example 1 14.5 14.3 14.6 Example 2 14.8 14.9 14.7 Example 3 15.1 14.9 15.2 Comparative Example 1 13.2 13.1 13.3 Comparative Example 2 13.9 14.1 13.8 Comparative Example 3 13.6 13.7 13.6 Comparative Example 4 10.1 10.3 10.5

[0081] It can be seen from Table 2 that the tensile strength of the composite materials for sustainable food packaging prepared in the embodiments is greater than that of comparative examples 1-4, which can prove that the modified rice bran wax and cinnamaldehyde are combined with polyvinyl alcohol to prepare a high oxygen and moisture barrier coating, and the mechanical properties of the composite materials for sustainable food packaging can be improved. At the same time, it can be proved that the high-strength film material solution prepared with silk fibroin as the main raw material, fumaric acid as a cross-linking agent, polyvinyl alcohol and corn starch nanocrystals can greatly improve the mechanical properties of the composite materials for sustainable food packaging.

[0082] Experiment 3: The surface-treated PET substrate and PET substrate prepared in the embodiment were taken, and the surface tension was tested using a surface tension tester. The tests were conducted three times respectively, and the data were recorded and tabulated. As shown in Table 3, it can be seen that the surface tension of the surface-treated PET substrate prepared in the embodiment is much higher than that of the PET substrate, and both are higher than 55 dyn / cm, which fully meets the requirements of coating adhesion.

[0083] Table 3: Surface tension of surface treated PET substrates

[0084] Surface tension dyn / cm first Second time The third time Example 1 54 56 53 Example 2 55 57 56 Example 3 57 58 56 PET substrate 40 42 41

[0085] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing a composite material for food packaging that can be used sustainably, characterized in that: The following steps are involved: S1: Preparation of high oxygen and moisture barrier coatings The rice bran wax is melted and filtered, and then coated on the surface of the carrier, and then cooled to obtain a rice bran wax film, 3-aminopropyl triethoxysilane is mixed with anhydrous ethanol, and then an acid reagent is added, and stirred to obtain an APTES solution, and the rice bran wax film is immersed in the APTES solution, stirred and then allowed to stand, and then filtered to obtain a solid, and the solid is washed and dried to obtain a modified rice bran wax, and the modified rice bran wax and cinnamaldehyde are added to deionized water, and the temperature is increased and stirred in a water bath to obtain a premixed liquid, polyvinyl alcohol is dissolved in hot deionized water to obtain a polyvinyl alcohol solution I, and nano ZnO is ultrasonically dispersed in deionized water to obtain a ZnO dispersion, and then the polyvinyl alcohol solution I and the ZnO dispersion are uniformly mixed to obtain a suspension, the suspension and the premixed liquid are uniformly mixed and stirred, and the pH is adjusted and then heated in a water bath, and then ultrasonically treated to obtain a high oxygen and moisture barrier coating; S2: Preparation of high-strength membrane solution The silk is placed in a Na2CO3 aqueous solution for heating treatment, washed and dried to obtain degummed silk, the degummed silk is added to a dissolving solution, heated and stirred until completely dissolved to obtain a silk fibroin mixed solution, the silk fibroin mixed solution is dialyzed with deionized water to obtain a silk fibroin aqueous solution, polyvinyl alcohol is dissolved in deionized water to obtain a polyvinyl alcohol solution II, corn starch nanocrystals are ultrasonically dispersed in deionized water to obtain a corn starch nanocrystal dispersion, the silk fibroin aqueous solution and the polyvinyl alcohol solution II are uniformly mixed, fumaric acid is added and stirred, and then glycerol and the corn starch nanocrystal dispersion are added for high-speed shearing, and a high-strength membrane material solution is obtained after standing. S3: Surface treatment and film coating of PET substrate The PET substrate is cleaned and subjected to graded corona treatment to obtain a surface-treated PET substrate. A high-strength film material solution is evenly coated on the surface of the surface-treated PET substrate using a coating rod. After drying, a film-coated PET substrate is obtained. A coating rod is then used to evenly coat the oxygen and moisture high barrier coating on the surface of the film-coated PET substrate. Drying is continued to obtain a sustainable composite material for food packaging.

2. The process for preparing a composite material for sustainable food packaging according to claim 1, characterized in that: Step S1: Preparation of oxygen and moisture high barrier coating, comprising the following steps: S1.1: Heat the rice bran wax until it is completely melted, filter to remove impurities, and then evenly coat the wax on the surface of the carrier by roller coating, controlling the coating thickness to be 1-2 mm, and obtain a rice bran wax film after cooling to room temperature, and place 3-aminopropyltriethoxysilane and anhydrous ethanol in a volume ratio of 1: (20-30) in a container, then add 1-2 wt % of an acid reagent, and stir evenly to obtain an APTES solution; S1.2: Immerse the rice bran wax film in the APTES solution, stir for 20-30 minutes, let stand for 1-1.5 hours, and then filter to obtain a solid, rinse the solid with anhydrous ethanol for 1-2 minutes, rinse it in deionized water for 2-3 times, and then dry it in a drying oven at a temperature of 40-45° C. for 2-3 hours to obtain modified rice bran wax, add 1-2 parts by weight of modified rice bran wax and 0.4-0.5 parts by weight of cinnamaldehyde to 30-40 parts by weight of deionized water, and stir it in a water bath at 50-55° C. for 50-60 minutes to obtain a premix; S1.3: Dissolve 12-15 parts by weight of polyvinyl alcohol in deionized water at 95-98°C to prepare a polyvinyl alcohol solution I with a mass fraction of 20-25%. Mix 1-1.5 parts by weight of nano ZnO and 50-60 parts by weight of deionized water in an ultrasonic cleaning machine and ultrasonicate at a frequency of 25-30kHz for 10-12 minutes to obtain a ZnO dispersion. Then, the polyvinyl alcohol solution I and the ZnO dispersion are mixed at a ratio of 1: The mixture is placed in a container with a mass ratio of (0.8-1), stirred for 25-30 minutes to obtain a suspension, and the premixed liquid and the suspension prepared in step S1.2 are uniformly stirred at high speed, and the pH is adjusted to 2-3, and then placed in a water bath, heated at a water bath temperature of 60-65°C for 1-2 hours, and then ultrasonicated at an ultrasonic frequency of 25-30 kHz for 20-30 minutes to obtain a high oxygen and moisture barrier coating.

3. The process for preparing a composite material for sustainable food packaging according to claim 2, characterized in that: Step S2 prepares a high-strength membrane material solution, comprising the following steps: S2.1: placing silk in a 0.05-0.06% Na2CO3 aqueous solution, heating at 98-100°C for 30-35 minutes, repeating 2-3 times, washing with deionized water and drying to obtain degummed silk, adding the degummed silk to the dissolving solution, stirring at 70-75°C until the degummed silk is completely dissolved, obtaining a fibroin mixed solution, placing the fibroin mixed solution into a dialysis bag, dialyzing with deionized water for 4-5 days, obtaining a fibroin aqueous solution; S2.2: dissolving polyvinyl alcohol in deionized water at 95-98° C. to prepare a 5-6 wt % polyvinyl alcohol solution II, and then placing corn starch nanocrystals and deionized water in an ultrasonic disperser, and ultrasonically dispersing them at an ultrasonic frequency of 25-30 kHz for 10-15 minutes to prepare a 0.6-0.8 wt % corn starch nanocrystal dispersion; S2.3: Mix the silk fibroin aqueous solution and polyvinyl alcohol solution II in a volume ratio of 1:(0.8-1) in a container, stir evenly and add fumaric acid. After stirring for 1-2 hours, add glycerol and corn starch nanocrystal dispersion, shear at a speed of 2000-3000 rpm for 40-45 minutes, and then let it stand for 2-3 hours to obtain a high-strength membrane solution.

4. A process for preparing a composite material for food packaging that can be used sustainably according to claim 3, It is characterized in that Step S3: Surface treatment of PET substrate and film coating, including the following steps: S3.1: Clean the surface of the PET substrate, then place it in a corona machine, set the distance between the electric blade and the PET substrate to 4-5mm, the voltage to 6-8kV, the pulse frequency to 32-35kHz, start the corona machine for 10-15 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 6-8mm, the voltage to 8.5-9kV, the pulse frequency to 20-25kHz, start the corona machine for 10-12 minutes of corona treatment, then change the distance between the electric blade and the PET substrate to 10-12mm, the voltage to 9.5-11kV, the pulse frequency to 18-20kHz, start the corona machine for 15-20 minutes of corona treatment, and obtain a surface-treated PET substrate; S3.2: Use a coating rod with a wet film thickness of 8-10μm to evenly coat the high-strength film material solution on the surface of the surface-treated PET substrate, and then place it in a blower dryer for drying for 12-15 hours to obtain a coated PET substrate. Then use a 6-8μm coating rod to evenly coat the oxygen and moisture high barrier coating on the surface of the coated PET substrate, and continue to place it in a blower dryer for drying for 10-12 hours to obtain a sustainable composite material for food packaging.

5. The process for preparing a composite material for sustainable food packaging according to claim 2, characterized in that: The acid reagent in step S1.1 is acetic acid.

6. The process for preparing a composite material for sustainable food packaging according to claim 2, characterized in that: The stirring speed of the high-speed stirring in step S1.3 is 1200-1500 rpm.

7. The process for preparing a composite material for sustainable food packaging according to claim 2, characterized in that: In step S1.3, the pH is adjusted by adding a hydrochloric acid solution with a concentration of 20-25%.

8. The process for preparing a composite material for sustainable food packaging according to claim 3, characterized in that: The dissolving solution in step S2.1 is prepared from CaCl2, ethanol and water in a molar ratio of 1:(2-3):(8-10).

9. The process for preparing a composite material for sustainable food packaging according to claim 3, characterized in that: In step S2.3, the fumaric acid accounts for 0.5-1% of the total mass of the silk fibroin aqueous solution and the polyvinyl alcohol solution, the glycerol accounts for 25-30% of the total volume of the silk fibroin aqueous solution and the polyvinyl alcohol solution, and the corn starch nanocrystal dispersion accounts for 40-50% of the total volume of the silk fibroin aqueous solution and the polyvinyl alcohol solution.

10. A sustainable composite material for food packaging, characterized in that: The food packaging composite material is prepared by the preparation process of a sustainable composite material for food packaging according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Oxidized bacterial cellulose reinforced fibroin antibacterial nano composite material and preparation method thereof

    CN114656737A

  • High-sealing-performance food packaging film and preparation method thereof

    CN116836441A

  • PET-bio-wax-SiO2 hydrophobic antibacterial electrospun food packaging film as well as preparation method and application of PET-bio-wax-SiO2 hydrophobic antibacterial electrospun food packaging film

    CN117306094A

  • Preparation method of biomass-based durable super-hydrophobic material

    CN118207750A

  • High barrier recyclable laminated film and preparation method thereof

    US12097686B1